METHODOLOGY FOR THE DEVELOPMENT OF THE COMPETENCE OF WORKING WITH INFORMATION IN PRIMARY EDUCATION - Qozoqboyeva Xanifaxon shavkatjon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Annotation: This article explores a comprehensive methodology for the development of competence in working with information in primary education. It delves into the significance of information competence, analyzes relevant literature, outlines effective methods, presents results, and engages in a critical discussion of the topic. The article concludes with key takeaways and suggestions for educators and policymakers.